Finite Element Analysis of Proximal Femur Bionic Nail (PFBN) Compared with Proximal Femoral Nail Antirotation and InterTan in Treatment of Intertrochanteric Fractures. Issue 9 (18th July 2022) - Wang, Yanhua; Chen, Wei; Zhang, Lijia; Xiong, Chen; Zhang, Xiaomeng; Yu, Kai; Ju, Jiabao; Chen, Xiaofeng; Zhang, Dianying; Zhang, Yingze
Abstract: Objective: To compare the biomechanical properties of proximal femur bionic nail (PFBN), proximal femoral nail antirotation (PFNA) and InterTan in the treatment of elderly intertrochanteric fractures AO/OTA 31‐A1.3 by finite element analysis. Methods: We used Mimics, Unigraphics and other software to establish normal femur and AO/OTA 31‐A1.3 fracture models, and reconstructed PFBN, PFNA and InterTan intramedullary nail models, and assembled them on the fracture model. The ANSYS software was used to compare the femoral von Mises stress distribution, deformation distribution, and internal fixation stress distribution of each group under a load of 2100 N. Results: It could be seen that the femoral maximum stress, femoral maximum displacement, and maximum stress of internal fixation of the PFBN group were lower than those in the PFNA group and the InterTan group. The maximum femoral stress of the PFBN was 190.25 MPa, while the maximum stress of the femur of the PFNA and InterTan groups were 238.41 Mpa and 226.97 Mpa. The maximum femoral displacement of each group were located at the top of the femoral head, and the maximum displacement of the PFBN group was 14.373 mm, and the maximum displacement values of the PFNA and InterTan groups were 19.49 and 15.225 mm. For the stress distribution of intramedullary nail, the maximum stress of the three kinds of internal fixation was located on the main nail. The maximum stress of PFBN was 1191.8 MPa, compared with 2142.8 MPa for PFNA and 1702.3 MPa for InterTan. And the maximum stress on the PFBN pressure nail was 345.35 MPa, compared with 868.6 MPa for the PFNA spiral blade and 545.5 MPa for InterTan interlocking twin nails. Conclusion: Compared with PFNA and InterTan, PFBN has better mechanical properties. The biomechanical characteristics of PFBN are more advantageous than PFNA and InterTan internal fixation system in the treatment of femoral intertrochanteric fractures. Abstract : We developed a new type of intramedullary fixation named Proximal Femur Bionic Nail (PFBN) and compared its biomechanical properties with Proximal Femur Bionic Nail(PFNA) and InterTAN by finite element analysis. The results showed that the femoral stress, femoral displacement and intramedullary nail stress in PFBN group were lower than those in PFNA group and InterTan group, and suggested PFBN is a promising new intramedullary nail.